After Negative Ethnicity: The Future of Voting in Kenya - Nikuze, Jean P. (Machakos University, 2018)
More than any other demographic, the question of negative ethnicity has been a scourge on the African continent. In Kenya, the ethnicisation of politics has plagued the nation since it gained its independence from the British. Ethno-politics persisted and reached its zenith in the 2007 postelection violence which left more than 1000 people dead. This paper interrogates ethnicity’s ties to geography; the power inhering in its situatedness. Using Appadurai’s concept of ‘deterritorialization’ and Appiah’s ‘cosmopolitanism’ the paper problematizes the idea that the space within ethnic boundaries is home in a bid to illustrate how the more open, transferable concept “good place that is no place” of Utopianism can help Kenyans detach from a localization. The adoption of this concept as a frame of reference would then disrupt the ethnic voting patterns of ethno-politics and finally usher in the age of voting based on issues and ideas.
Keywords: Negative Ethnicity; Kenya Election